Substitusi Tepung Ikan Dan Tepung Bungkil Kedelai Dengan Tepung Daun Indigofera (Indigofera zollingeriana) Dalam Ransum Terhadap Performa Produksi Ayam Broiler - Ardhika Akbar, Rizky; Widianingrum, Dini; Falahudin, Aaf (Study Program of Animal Husbandry, Faculty of Agricultural, Universitas Majalengka, 2025)
The success of broiler production is expressed in its production performance. The achievement of broiler performance is influenced by management. Feed management factors play an important role in determining the success of broiler farming. The purpose of this study was to analyse the effect of substitution of fish meal and soybean meal with indigofera leaf meal (TDI) in the ration on broiler production performance, and to get the balance of substitution of fish meal and soybean meal with indigofera leaf meal (TDI) in the ration to determine the best broiler production performance. The research was conducted experimentally using a completely randomised design (CRD). The treatment types used were P0 (Ration without TDI) as control, P1 (Ration + 25% TDI), P2 (Ration + 30% TDI) P3 (Ration + 35% TDI), P4 (Ration + 40% TDI). Variables observed included daily ration consumption, daily body weight gain, ration conversion, feed cost per gain, and mortality. Data from the study were analysed using analysis of variance and if it showed significant differences, it was further tested using Duncan's multiple range test. The results showed that daily ration consumption, daily body weight gain, ration conversion, and feed cost per gain with the addition of indigofera leaf meal in the ration statistically showed significant differences while mortality only occurred.